A Review on the Development of a Track Irregularity Measurement Tool - Febrian Angga Prasetyo; Satrio Wicaksono (The Islamic Education and Multiculturalism Foundation, 2023)
Railway transportation is one of the most vital transportation modes for people and goods. Ensuring railway transportation safety and efficiency is very important. The condition of the track is one of the most vital factors in ensuring railway safety, as irregularities in the track can lead to severe accidents. Thus, it is essential to have proper gauges and methods to measure track irregularities. This paper will discuss different methods to measure track irregularities and their advantages and limitations. Several track irregularity measurement tools will be divided into groups based on different aspects, such as the contact types and their location. Contact methods can measure more detailed irregularities, but have limitations such as injury and equipment damage. Non-contact methods are less invasive and can measure larger rail sections, but are less accurate. The inspection method will be chosen based on the track configuration that must be carefully studied to ensure the most efficient and effective inspection methods for a rail type. Regardless of the method, it is important to keep developing and improving existing track irregularity measurement tools to increase efficiency and reduce measurement errors.